2020
DOI: 10.1111/jdi.13464
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular events and mortality in people with and without type 2 diabetes: An observational study in a contemporary multi‐ethnic population

Abstract: Aims/Introduction The aim of this study was to examine ethnicity‐specific associations between type 2 diabetes mellitus and the risk of a cardiovascular disease (CVD) event as well as risk of specific CVD phenotypes in England. Methods We obtained data from the Clinical Practice Research Datalink for adults with and without type 2 diabetes mellitus diagnosed 2000–2006. The outcome was the first CVD event during 2007–2017 and the following components: aortic aneurysm, cerebrovascular accidents, heart failure, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 29 publications
2
20
0
1
Order By: Relevance
“…Based on our OGTT results, BGP is not likely to exert the aforementioned prevention by settling glucose homeostasis; although, some significant differences were demonstrated in our present study (Figures 3, 4), instead the action of it might have some relationship to oxidative stress. Diabetes, even type II diabetes, is associated with higher risk of mortality (Coles et al, 2020), probably due to the accompanying oxidative stress (Rosales-Corral et al, 2015), which is proven to be among the causes of macro-and microcirculatory complications of diabetes (Madonna et al, 2017;Frisbee et al, 2019). Although at this point we have little information on the exact mechanism of action of BGP-15, it is at least a very telling result that no BGP-treated animals died during the 12 months spent in diabetes.…”
Section: Discussionmentioning
confidence: 98%
“…Based on our OGTT results, BGP is not likely to exert the aforementioned prevention by settling glucose homeostasis; although, some significant differences were demonstrated in our present study (Figures 3, 4), instead the action of it might have some relationship to oxidative stress. Diabetes, even type II diabetes, is associated with higher risk of mortality (Coles et al, 2020), probably due to the accompanying oxidative stress (Rosales-Corral et al, 2015), which is proven to be among the causes of macro-and microcirculatory complications of diabetes (Madonna et al, 2017;Frisbee et al, 2019). Although at this point we have little information on the exact mechanism of action of BGP-15, it is at least a very telling result that no BGP-treated animals died during the 12 months spent in diabetes.…”
Section: Discussionmentioning
confidence: 98%
“…Our results emphasise the need for conducting body composition analysis in screening for CAD. Since the relative risk of CAD is linked (20–50%) with higher mortality in the Asian Indian population in comparison to other populations, 33 it necessitates the presence of robust screening strategies along with health education and awareness to improve health.…”
Section: Discussionmentioning
confidence: 99%
“…country [4]. Furthermore, CVD eventssuch as heart failure and myocardial infarctiontend to occur earlier in South Asians compared to other ethnicities [5][6][7][8][9]. More limited and contrasting is the evidence about the prognosis following a CVD event: initial, very small studies in the UK have suggested higher mortality rates in South Asians compared to White Europeans following a myocardial infarction [10], while more recent observations, based on much larger samples, have reported a similar [7,9,11] or lower [12] risk.…”
Section: Introductionmentioning
confidence: 99%
“…More limited and contrasting is the evidence about the prognosis following a CVD event: initial, very small studies in the UK have suggested higher mortality rates in South Asians compared to White Europeans following a myocardial infarction [10], while more recent observations, based on much larger samples, have reported a similar [7,9,11] or lower [12] risk. Detailed UK data on the risk of a first CVD event and the prognosis following the event are more limited for other ethnic groups [8,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%